Etika Interaksi Guru dan Murid Dalam Menyayangi dan Menghormati - Ardina Khoirunnisa; Ira Suryani; Bella Azahra; Nur Adila; Nurul Fadilah Nst; Nurul Fadillah (EduInovasi: Journal of Basic Educational Studies, 2023)
According to his research, student ethics towards teachers include sitting in front of the teacher, speaking politely, not interrupting the teacher's conversation, listening to what the teacher is saying, asking gently and respectfully if you don't understand, attending every day, not skipping classes or falling asleep for no apparent reason. , enter the class before the teacher enters, and follow the teacher's instructions. According to him, ethics cannot be simply taught; rather, they must be internalized through habit and example. In this case we discuss the ethics of a student towards the teacher and vice versa in the context of saying love and respecting each other and in the end this article also materializes because nowadays there is a lack of ethics in everyday life so to know all of these things we must first know what is the nature of ethics and what ethics and morals are related and how these ethics are Keywords: ethics, teachers, compassion, students